Analisis Perilaku Buang Air Besar Sembarangan (BABS) Di Kelurahan Batu Kuning Wilayah Kerja UPTD Puskesmas Tanjung Agung Kecamatan Baturaja Barat Kabupaten Oku Tahun 2022 - Wiwiet Susan Amelia; Lilis Suryani; Ali Harokan; Maria Ulfah (HEALTH CARE : JURNAL KESEHATAN, 2022)
Open defecation is an unhealthy behavior and can cause disease in the community. This study aimed to determine the factors associated with open defecation in Batu Kuning Village, Tanjung Agung Health Center Working Area, West Baturaja District, OKU Regency in 2022. It was a quantitative with cross sectional design. The population in this study was the head of the family in Batu Kuning Village, Tanjung Agung Public Health Center, Baturaja Subdistrict, in 2022. The sampling method used in this study was random sampling. The sample of this research was 93 respondents. A questionnaire was distributed to collect the data. Statistical test analysis by using the chi-square test showed there was a significant relationship (p < 0.05) for knowledge (p value 0.000), attitude (p value 0.000), latrine conditions (p value 0.000) and clean water sources (p value 0.000) , there was no relationship between age (p value 0.251) and income (p value 0.588). From the results of the multivariate analysis, it was found that the dominant factor for open defecation in Batu Kuning Village, Tanjung Agung Health Center Working Area, Baturaja Barat District, OKU Regency in 2022, namely attitude (p value 0.000) (OR 1.012). There was a relationship significant (p < 0.05) for knowledge, attitude, condition of latrines and clean water sources, there was no relationship between age and income. The dominant factor in open defecation in Batu Kuning Village, Tanjung Agung Health Center Working Area, Baturaja Barat District, OKU Regency in 2022, namely attitude.